Bringing to Life the World’s Tallest Structure - Jonathan Weigand (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2013)
Intended as the centerpiece of constructional developments in Dubai, the Burj Khalifa now stands as the tallest building ever constructed. The uniquely designed foundation consists of a concrete raft supported by a cast-in-place pile system protected by waterproofing membrane to inhibit corrosion. The structural design integrates high-performance reinforced concrete and steel and incorporates an engineered “Y” shape that limits the lateral wind pressure on the building. Engineers applied the latest advancements in high-rise technology to develop an optimized construction plan that consisted of segmented tasks that promoted the staff to work at a quick yet manageable pace. This article details the innovative techniques involved in the foundation construction, overall structural design, wind engineering, and construction planning of the Burj Khalifa.
Keywords: Burj Khalifa; Construction; Concrete